PENGARUH KEADILAN ORGANISASIONAL DAN KETERLIBATAN KERJA TERHADAP KOMITMEN ORGANISASI PADA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KERINCI - Ayu Esteka Sari; Faisal Amri (Gapenas Publisher, 2022)
This study aims to find out how the Effect of Organizational Justice and Work Engagement on Organizational Commitment to the Staff of the Population and Civil Registration Office of Kerinci Regency. The technique of collecting data using a questionnaire after testing the validity and reliability. Data analysis techniques are carried out using, multiple linear regression analysis, hypothesis testing, coefficient of determination (R2). The results of this study indicate that: There is a significant effect between Organizational Justice on Organizational Commitment to the Staff of the Population and Civil Registration Office of Kerinci Regency, this is evidenced by t count> t table (3.431> 2.04227). There is a significant influence between Organizational work involvement on Organizational Commitment to the Staff of the Population and Civil Registration Office of Kerinci Regency, this is evidenced by t count> t table (4,192> 2,04227). There is the influence of organizational justice and work involvement affect the organizational commitment of the Department of Population and Civil Registration Staff Kerinci Regency simultaneously, this is evidenced by F count> Ftable (15,049> 3,32). The magnitude of the influence of organizational justice and work involvement on organizational commitment in the Department of Population and Civil Registration staff of Kerinci Regency is 50.1%, while the remaining 48.9% is explained by other causal factors not examined in this study